Assessment ploidy level, genetic relationship by rapd markers of progenies and parental lines in Hippeastrum - Thu Huong, Bui Thi; Tuong, Ho Manh; Son, Le Van; Hoa, Nguyen Hanh (Academia Journal of Biology, 2014)
Hippeastrum is one of the most beautiful flowers and widely growed in Vietnam. In some recent years, number of people loving Hippeastrum is increasing. That is the result why Hippeastrum breeding is a necessary task today. However, the identification and early detection of hybrid Hippeastrum in Vietnam is difficult work. Therefore, the application of molecular markers would solve this challenge. In this study, nine RAPD markers were used to assess five suspected hybrid (H1, H12, H3, H85, H5) of three Hippeastrum crosses (ĐN x TR, TR x ĐST, ĐST x ĐN). The results successfully show that H1 is identified hybrid of crosses of ĐN x TR; H12, H85 are the hybrid of ĐST x TR cross and H3, H5 are hybrid progenies of ĐST x ĐN cross. In addition, the study also analyzed ploidy level of parents and progenies of three hybrid crosses that supports for the selection and breeding in other researches. The results show that five hybrid progenies and three parental Hippeastrumsts have 2n ploidy level.